Optimization of two natural coagulants co-adjuved by sodium hydroxide for the potabilization of water from the Caplina river - Tirado Paz, Eleocadio Dionisio (2022)
Natural coagulants are a viable alternative to accelerate sedimentation in the water purification process, with certain benefits such as the generation of nutrient-enriched sludge to be used later and safety against the environment, unlike chemical coagulants. Therefore, the present study aimed to: Optimize the doses of moringa (Moringa oleifera) and cassava starch (Manihot esculenta) assisted by sodium hydroxide as coagulants for the purification of waters from the Caplina River in Tacna. A multilevel factorial design of 5 x 5 x 3 was carried out with a total of 75 experimental units and the variables were evaluated: pH and sedimentation time. The yield of moringa and cassava for the preparation of coagulants was 75% and 15.6%, respectively. It was determined that, at a concentration of NaOH at 0.0049 M, 3.2 g / L of cassava starch and 0.1 g / L of moringa seed powder, the optimal dose will be obtained with a pH of the treated water of 6.6 and a time sedimentation of 6 minutes. It was concluded that this conventional chemical coagulant can be partially substituted.